Env-Specific IgA from Viremic HIV-Infected Subjects Compromises Antibody-Dependent Cellular Cytotoxicity - Ruiz, María Julia; Ghiglione, Yanina; Falivene, Juliana; Laufer, Natalia; Holgado, María Pía; Socías, María Eugenia; Cahn, Pedro; Sued, Omar; Giavedoni, Luis; Salomón, Horacio; Gherardi, María Magdalena; Rodríguez, Ana María; et al. (Journal of virology, 2016)
Elucidating the factors that modulate HIV-specific antibody-dependent cellular cytotoxicity (ADCC) will help in understanding its role in HIV immunity. The aim of this study was to determine whether IgA could modify the magnitude of ADCC in HIV infection, abrogating its protective role. Plasma samples from 20 HIV-positive (HIV(+)) subjects enrolled during primary HIV infection (PHI), 10 chronically infected subjects (chronic), and 7 elite controllers (EC) were used. ADCC was determined by using a fluorometric ADCC assay, before and after removal of plasma IgA. Data were analyzed by using nonparametric statistics. ADCC was documented in 80% of PHI enrollment samples and in 100% of PHI 12-month, chronic, and EC samples; it peaked after acute infection, reached a plateau in chronic infection, and decreased after initiation of antiretroviral treatment (ART). Significant associations between ADCC and disease progression were found only after removal of plasma IgA from 12-month PHI samples: the magnitude of ADCC not only increased after IgA removal but also correlated with CD4(+) T-cell preservation. This work provides evidence that gp120-specific IgA was capable of modifying ADCC responses during natural HIV infection for the first time and adds to similar evidence provided in other settings. Furthermore, it underscores the complexity of the ADCC phenomenon and will help in an understanding of its underlying mechanisms. Although the induction of ADCC-mediating antibodies in HIV-infected subjects has been extensively documented, the association of these antibodies with protection from disease progression is poorly understood. Here, we demonstrate that plasma IgA is a factor capable of modifying the magnitude of IgG-mediated ADCC in HIV infection, mitigating its beneficial effect. These results help in understanding why previous studies failed to demonstrate correlations between ADCC and disease progression, and they also contribute to the notion that an HIV vaccine should stimulate the production of ADCC-mediating IgG antibodies but not IgA.